Roles of extracellular polymeric substances in the bactericidal effect of nanoscale zero-valent iron: trade-offs between physical disruption and oxidative damage. Issue 7 (6th June 2019) - Hu, Ying; Wang, Jian; Sun, Hongwei; Wang, Shaohui; Liao, Xiaomei; Wang, Jun; An, Taicheng
Abstract : Increased EPS encountered trade-offs between enhanced membrane disruption and decreased oxidative damage to mitigate the bactericidal effect of nZVI. Abstract : Nanoscale zero-valent iron (nZVI) was known to inactivate various microbes, but the impact of extracellular polymeric substances (EPS) on the bactericidal effect of nZVI remained poorly understood. In this study, we seek to clarify the role of capsular EPS in nZVI inactivation of Escherichia coli under aerobic conditions, by employing parental and isogenic mutants with controlled EPS secretion for comparison. The results indicated that increased EPS of E. coli mitigated the toxicity of nZVI. Surprisingly, more EPS favored the adsorption of nZVI on the E. coli surface, and subsequently resulted in enhanced membrane disruption, which contradicted the E. coli inactivation trends. Nonetheless, E. coli was able to repair the damaged membrane partially with nutrient supply; besides, EPS accelerated the corrosion of nZVI to produce less toxic iron (hydro)oxides. More importantly, EPS could scavenge reactive oxygen species (ROS) produced by oxygenation of nZVI, and prevent ROS from penetrating the cell membrane to damage intracellular structures and macromolecules. Therefore, by increasing EPS secretion, E. coli made trade-offs between physical disruption and oxidative damage to improve the resistance to nZVI inactivation. Besides, similar roles of EPS were also observed in the Gram-positive bacterium Bacillus subtilis . These findings broadened our understanding of the bactericidal mechanism of nZVI, which would benefit the environmental risk assessment of nZVI and the development of ZVI based water disinfection techniques.